Effects of Invasive Alien Plant Species (IAPS) on Native Plant Species in Three Different Altitudinal Range: A Case Study of Five Community Forests of Jajarkot District - Shrestha, Prerana; Mandal, Ram Asheshwor; Kandel, Prashid; Rajbhandari, Sujan; Sharma, Garima; Mahat, Niraj; Poudel, Sanjay; Dahal, Deepa; Budhathoki, Arati; Basnet, Reecha (Journal of Forest and Livelihood, 2025)
Invasive Alien Plant Species (IAPS) pose significant threats to biodiversity and ecosystem services, particularly in ecologically sensitive regions like Nepal. This study investigates the distribution and ecological impacts of IAPS across altitudinal gradients in the Jajarkot district, with a focus on forest ecosystems and agricultural landscapes. Field surveys employing quadrat plots identified four dominant IAPS, notably Ageratina adenophora and Bidens pilosa, which were more distributed across altitudes. Biodiversity indices, such as the Shannon-Weiner index, indicated impact of IAPS in distribution of native species. The Importance Value Index (IVI) revealed IAPS dominance at lower altitudes, contributing to reduce in frequency of native species and ecosystem destabilisation. The spread of IAPS was closely linked to human disturbances, decreased canopy cover and increased IAPS cover suggesting that these factors may facilitate, their upward expansion under changing environmental conditions. Our study had uneven plot distribution and a research focus on community forest as a limitations. The findings underscore the urgent need for integrated IAPS management. Strategies should prioritise targeted interventions, including community engagement, sustainable forest management practices, and policy reforms, to mitigate IAPS spread and safeguard biodiversity along altitudinal gradients.